Housing Policy Systems in South and East Asia
XVI, 191 p.
Keywords: This book provides an up-to-date account of housing policy systems in eight countries - Hong Kong, Indonesia, Japan, Korea, Malaysia, Taiwan, Thailand and Singapore. With one chapter devoted to each country, there are, in addition, introductory and concluding chapters, in which the editors identify both the similarities in the problems faced, and in the approaches adopted, by the governments of the Asian countries - setting them apart from the West - as well as the differences that indicate the variety of Asian solutions.